The Cambridge Companion to Joseph Ratzinger. Edited by Daniel Cardó and Uwe Michael Lang - Doyle, Dennis M. (The journal of theological studies, 2025)
Although the late Joseph Ratzinger (Pope Benedict XVI) produced a tremendous output of writings both as an academic and as pope, the authors of the essays